Analisis Pengaruh Kurs Rupiah dan Inflasi Terhadap Net Ekspor - Soelehan, Aan; Marpaung, Annaria Magdalena (LPPM Institut Bisnis dan Informatika Kesatuan, 2013)
The purpose of this research is to find out the direct or indirect effect of rupiah exchange rate and inflation on net export. The method used for this research is path analysis method. The independent variable is exchange rate and inflation, while the dependent variable is net export. The intervening variable is gross domestic product (GDP) deflator and foreign exchange reserve. Based on the result of this research, it can be found out the direct effect of exchange rate on foreign exchange reserve and the direct effect of foreign exchange on net export. In another side, there are direct effect of inflation to PDB deflator and PDB deflator to net export. The conclusion yielded shows that there are indirect effect of exchange rate and inflation to net export. Keywords: exchange rate; inflation; GDP deflator; foreign exchange; net export